2016
DOI: 10.1614/wt-d-16-00011.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Postemergence Herbicides, Safener, and Tolerant Hybrids for Corn Response

Abstract: Crop safety is one of the many considerations when deciding which POST herbicide to use. This research examined relative corn injury as a result of POST herbicides and the effect of including the safener isoxadifen, the choice of a sensitive or tolerant hybrid, or both. The herbicides included commercial combinations of dicamba, diflufenzopyr, nicosulfuron, rimsulfuron, and thifensulfuron, all at twice the labeled rate. Isoxadifen reduced twisting from dicamba plus diflufenzopyr but not with dicamba plus rimsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…They exhibit excellent herbicidal effects on a broad range of weeds. Nevertheless, the phytotoxicity of sulfonylurea herbicides on nontarget crops has been reported [1,2]. According to a survey, after the application of chlorsulfuron, crop damage and yield decline can occur [3].…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit excellent herbicidal effects on a broad range of weeds. Nevertheless, the phytotoxicity of sulfonylurea herbicides on nontarget crops has been reported [1,2]. According to a survey, after the application of chlorsulfuron, crop damage and yield decline can occur [3].…”
Section: Introductionmentioning
confidence: 99%
“…Corn yields were reduced by 11 to 16 bu/acre with both the 1× and 2× rates of nicosulfuron + rimsulfuron + isoxadifen and thiencarbazone + tembotrione + isoxadifen, when compared with the NTC (Table 3). Recently, VanGessel et al (2016) reported similar reductions in corn grain yield with combinations of rimsulfuron and isoxadifen. In other research, thiencarbazone + tembotrione + isoxadifen did not reduce grain yield of tolerant field corn hybrids (Stephenson et al, 2015).…”
Section: Aboveground Biomass Plant Height and Grain Yieldmentioning
confidence: 79%
“…However, the four corn hybrids in that test are not adapted to the southeastern United States. A more recent study showed that crop safety can be improved when isoxadifen is included in ALS‐herbicide formulations (VanGessel et al, 2016). However, this improvement in crop safety was not consistent and only one sensitive hybrid and one tolerant hybrid were tested.…”
Section: Sulfonylurea/als Herbicides and The Crop Safener Isoxadifenmentioning
confidence: 99%
See 2 more Smart Citations